Z dziejów polonistyki szkolnej: Alojzy Osiński = From the history of Polish studies at primary school - Kulka, Bronisława (Zielona Góra: Wyższa Szkoła Pedagogiczna)
In the years 1800-1830 Polish language gained status of a separata subject at secondary schools, but due to political situation its place at school varied in each annexed territory of partitioned Poland. Famaus Polish secondary school in town of Krzemieniec worked to its advantage up to 1830. School teen-agers were educated in a patriotic and democratic spirit.
Keywords: Osiński, Alojzy (1770?-1842); dydaktyka literatury; 19 w.